Development of a national cosmic-ray dose monitoring system with Health Canada's Fixed Point Surveillance network. (October 2018) - Liu, Chuanlei; Zhang, Weihua; Ungar, Kurt; Korpach, Ed; White, Brian; Benotto, Mike; Pellerin, Eric
Abstract: This work explores the application of Health Canada's Fixed Point Surveillance (FPS) network for cosmic ray monitoring and dose estimation purposes. This network is comprised of RS250 3 inch by 3 inch Sodium Iodide (NaI) spectroscopic dosimeters distributed throughout Canada. The RS250's high channel count rate responds to the electromagnetic and muonic components of cosmic ray shower. These count rates are used to infer cosmic ray doses throughout FPS locations. The derived dose was found to have an accuracy within 6.5% deviation relative to theoretical calculation. The solar cycle effect and meteorologically induced fluctuation can be realistically reflected in the estimated dose. This work may serve as a basis to enable the FPS network to monitor and report both terrestrial and cosmic radiation in quasi-real time. Highlights: The work explored the application of Health Canada's Fixed Point Surveillance network for cosmic ray dose estimation purpose. The cosmic doses derived from the response of the Sodium Iodide detectors in the network achieved accuracy within 6.5% relative to theoretical calculation. The work may serve as a basis to enable the network to monitor both terrestrial and cosmic radiation in quasi-real time.